Evaluasi Klinis Presisi POCT dan Chemistry Analyzer dalam Pemeriksaan Glukosa Darah Sewaktu Pasien Diabetes Melitus - Isnin Aulia Ulfah Mu’awanah; Zuvi Fridhoriansyah; Tirsayanti AD. Hamidi (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Diabetes mellitus (DM) is a global health problem with a steadily increasing prevalence, including in Indonesia. The International Diabetes Federation (IDF) 2021 reported that Indonesia ranks fifth worldwide with approximately 19.5 million people living with DM, projected to exceed 28 million by 2045. This situation highlights blood glucose testing as a key indicator for both diagnosis and therapy monitoring. Validation of measurement methods, either Point-of-Care Testing (POCT) or chemistry analyzer as the laboratory standard, is required to ensure result reliability before clinical implementation. This study aimed to evaluate the precision, agreement, and linear relationship between POCT and chemistry analyzer in random blood glucose testing of patients with type 2 DM. An experimental comparative design was conducted on 30 patients at Mokoyurli General Hospital, Central Sulawesi. Each blood sample was analyzed using both methods with three repetitions.The results showed mean %CV values of 0.83% for POCT and 0.26% for chemistry analyzer, both within the acceptable precision threshold (<2%). Bland–Altman analysis revealed a bias of –14.36 mg/dL with LoA ranging from –33.28 to 4.56 mg/dL. Pearson correlation demonstrated a very strong linear relationship (r = 0.985; p<0.001), while Lin’s CCC of 0.86 indicated moderate agreement. Linear regression identified constant bias (–12.08) and proportional bias (slope 0.95), with POCT consistently reporting lower values, particularly at higher glucose concentrations.Chemistry analyzer exhibited superior precision compared to POCT. Nevertheless, POCT provides clinically acceptable performance for rapid screening, though results at critical values should be confirmed using standard laboratory methods